Somatic embryogenesis in oil palm from immature leaves with emphasis on leaf position, sequential callus re-collection, use of temporary immersion system, and assessment of genetic and epigenetic fidelity of the resulting clones - Gomes, H.T.; Machado, L.G.; Bartos, P.M.C.; Da Silva Costa, F.H.; Azevedo, V.C.R.; De Araújo Silva Cardoso, I.M.; De Souza, A.L.F.; Inglis, P.W.; Scherwinski‐Pereira, J.E. (Springer, 2024)
In oil palm, somatic embryogenesis is one of the few methods available for clonal propagation of elite individuals that have already been phenotyped in the field. In this study, we evaluated somatic embryogenesis in immature leaves of adult oil palm plants, with particular focus on the use of temporary immersion systems, and analyzed the genetic and epigenetic fidelity of the resulting clones. Leaf segments identified as belonging to regions L1 to L8 of the heart of palm were cultured in MS medium supplemented with 450 µM Picloram, 0.5 g L− 1 glutamine, 30 g L− 1 sucrose, and 2.5 g L− 1 activated charcoal to induce callogenesis. The resulting calli were then multiplied using different culture systems: semi-solid, stirred liquid, recipient for automated temporary immersion (RITA®), and twin flask bioreactor. Subsequently, differentiation of somatic embryos was carried out in MS medium supplemented with 12.3 µM 2-iP and 0.54 µM NAA. The regeneration phase involved culturing calli with clusters of somatic embryos in the torpedo stage using semi-solid, RITA®, and twin flask systems. At the end of the culture, the genetic and epigenetic fidelity of the regenerated plants was evaluated by ISSR and MS-AFLP markers, respectively. The analysis revealed that callus formation occurred in all leaves except L1. However, leaves collected at L4, L5, and L7 showed significantly higher callus formation rates, averaging around 10%. Stirred liquid medium and the RITA® system exhibited the highest rates of fresh biomass and dry biomass growth for callus multiplication. In terms of regeneration, the best results were obtained with RITA® bioreactors, which led to an average of 14.1 plants per gram of inoculated material. With this system, no variations were observed in the DNA sequence of the regenerated plants, and indices of epigenetic methylation pattern changes as well as DNA hypomethylation rates were lower than in other tested systems.